2014
DOI: 10.1021/am500604p
|View full text |Cite
|
Sign up to set email alerts
|

Mn-Doped TiO2 Nanosheet-Based Spheres as Anode Materials for Lithium-Ion Batteries with High Performance at Elevated Temperatures

Abstract: Novel Mn(2+)-doped TiO2 nanosheet-based spheres have been successfully prepared via a simple hydrothermal and ion-exchange process. After hydrothermal growth, flowerlike nanosheet-based spheres of protonated dititanate were confirmed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The hierarchical nanostructure was obtained via a dissolution-recrystallization process starting from a precursor of homogenous TiO2 nanospheres. Moreover, as-prepared protonated dititanate was conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 53 publications
2
61
0
Order By: Relevance
“…Nyquist plots in Fig. 6D for the MHTiO 2 @CeAu and MHTiO 2 @C electrodes consist of a semicircle at the medium frequency region and a straight line low frequency, which is associated with the charge transfer resistance at the electrode-electrolyte interface and the lithium ion diffusion in the bulk of the electrode materials, respectively [44,45]. Compared with the MHTiO 2 @C electrode, EIS measurements taken before cycling for the MHTiO 2 @CeAu electrode displayed reduced semicircle size and increased slope of the straight line, which demonstrated the rapid electron transport and lithium ion diffusion, thereby realizing superior rate performance and cycling stability.…”
Section: Resultsmentioning
confidence: 99%
“…Nyquist plots in Fig. 6D for the MHTiO 2 @CeAu and MHTiO 2 @C electrodes consist of a semicircle at the medium frequency region and a straight line low frequency, which is associated with the charge transfer resistance at the electrode-electrolyte interface and the lithium ion diffusion in the bulk of the electrode materials, respectively [44,45]. Compared with the MHTiO 2 @C electrode, EIS measurements taken before cycling for the MHTiO 2 @CeAu electrode displayed reduced semicircle size and increased slope of the straight line, which demonstrated the rapid electron transport and lithium ion diffusion, thereby realizing superior rate performance and cycling stability.…”
Section: Resultsmentioning
confidence: 99%
“…It is demonstrated that heteroatoms substituted into the TiO 2 lattice can create dopant energy levels and fully modify the electronic structures such as B, N, S, Mn, Ni, and Sn. 13,18,14,17,24 On one hand, some interstitial oxygen defects and vancancies, or titanium vacancies are created as a result of the difference of ionic radius and electronegativies, which significantly improves the electrical conductivity and decreases the charge transfer resistance. On the other hand, the doping Mo 6+ ions with a larger radius (0.068 nm) can induce the increase of unit cell volume in the TiO 2 crystal structure as well as lattice distortion (Fig.…”
Section: Li-ion Storage Performance Referencesmentioning
confidence: 99%
“…3c), which facilitates more Li + ions to be inserted into the electrode materials for the high capacity. 14,17 Furthermore, because of the intriguing temperature gradient in flame, lots of ultrafine MoO 3 crystals are highly dispersed on the in situ Mo 6+ doped TiO 2 to generate novel heterojucntions by the high-temperature phasesegregation growth and unique sintering effects. 30,31 As high electrochemical activity components, Mo 6+ embedded into TiO 2 lattices and highly dispersed ultrafine MoO 3 crystals can provide the extra Li + ions storage ability through the conversion reaction (Equation 3).…”
Section: Li-ion Storage Performance Referencesmentioning
confidence: 99%
“…Numerous types of transition metals have already used TiO 2 for Li-ion batteries [20,21]. The electrical properties of TiO 2 can be improved by substituting Nb for Ti.…”
Section: Introductionmentioning
confidence: 99%